2017
DOI: 10.1590/s0100-204x2017000700004
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance of modern soybean cultivars in multi-environment trials

Abstract: The objective of this work was to evaluate the productive performance, and the adaptability and stability parameters of modern soybean (Glycine max) cultivars in multi-environment trials, as well as to identify the ideal genotypes for eight growing environments in Brazil. A randomized complete block experimental design was carried out, with three replicates, for the evaluation of 46 soybean cultivars in eight environments, in the microregions of adaptation 102, 201, and 202, in the 2014/2015 crop season. A com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
2
15
0
3
Order By: Relevance
“…These locations range from Pelotas in the extreme south of Rio Grande do Sul State to Guarapuava in Paraná State, with altitudes varying from 14 m to 1116 m asl (Table 1). Similar results for the variance components were reported by Lopez‐Cruz et al (2015) and Matei et al (2017) in their wheat and soybean METs.…”
Section: Discussionsupporting
confidence: 89%
“…These locations range from Pelotas in the extreme south of Rio Grande do Sul State to Guarapuava in Paraná State, with altitudes varying from 14 m to 1116 m asl (Table 1). Similar results for the variance components were reported by Lopez‐Cruz et al (2015) and Matei et al (2017) in their wheat and soybean METs.…”
Section: Discussionsupporting
confidence: 89%
“…Higher values of GY, OIL, PRT, PH, and TGW are desirable for soybean crop (Matei et al., ; Matei et al., ). Medium‐cycle cultivars have been prioritized because they present higher productive potential and are preferred by farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Leite et al (2018) indicated that exploratory multivariate techniques can be applied to select genotypes by analyzing the agronomic traits altogether, increasing the chance of success of a breeding program. Higher values of GY, OIL, PRT, PH, and TGW are desirable for soybean crop (Matei et al, 2017;Matei et al, 2018). Medium-cycle cultivars have been prioritized because they present higher productive potential and are preferred by farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Embora a precipitação total foi em quantidade suficiente para a cultura da soja, nas quatro épocas de semeadura, notou-se que houve distribuição irregular de chuva, especialmente na semeadura de janeiro, ocorrendo período de estiagem no florescimento e no enchimento de grãos, o que impactou a produtividade de grãos. Matei et al (2017) avaliaram o potencial de produção da cultivar NS 6909 IPRO.…”
Section: Methodsunclassified